Studi Eksperimental Nilai Marshall pada Campuran AC-WC Menggunakan Aspal Modifikasi Karet Alam Terhadap Variasi Suhu Pemadatan - Ikhlas Zai; Fitridawati Soehardi; Putri, Lusi Dwi (Universitas Lancang Kuning, 2025)
In this research, the modified asphalt used is natural rubber asphalt, which has high elastic properties due to its high resilience and high strain ratio. The aim of this research is to analyze the marshall value with variations in compaction temperature using natural rubber modified asphalt. The results of this research showed that the temperature variation density value increased with the highest temperature density at 160℃ of 2.17 gr/cm and the lowest value at 110℃ of 1.91gr/cm. The Marshall value of the VFWA value increased with the highest increase at a temperature variation of 160℃ of 68.1% and the lowest value at a temperature of 110℃ of 31.5%. The VITM value relative to the Marshall value tends to decrease with the lowest decrease at a temperature variation of 160℃ of 3.20% and the highest value at a temperature of 110℃ of 5.67%. The VMA value of the temperature variation relative to the Marshall value tends to decrease at a temperature of 160℃ of 28. 39% and the largest value is at a temperature of 110℃ of 36.91%. The stability value at temperature variations on Marshall characteristics tends to increase with the highest increase at a temperature of 160℃ of 1702.49 and the smallest value at a temperature variation of 110℃ of 1323.41. The MQ value in temperature variations with respect to the Marshall characteristics increased at a temperature of 140℃ by 523.90mm and the lowest value at a temperature of 110℃ was 183.81 mm. Marshall characteristics with respect to flow values ​​tended to fluctuate with the highest increase at a temperature variation of 120℃ of 7.80mm. and the lowest at a temperature of 160℃ is 2.23mm. So, with each increase in compaction temperature, the marshall value at a temperature variation of 140℃ - 160℃ with the use of natural rubber modified asphalt meets the requirements of Bina Marga specifications.